The water jet guided laser method in punching honeycomb cores for Aerospace sandwich panels - Холодный, Владимир Юрьевич; Саленко, Александр Федорович (Eastern-European Journal of Enterprise Technologies, 2016)
The study shows the options and proves feasibility of applying the water jet guided laser method in perforating 55 micron-thick aluminum foil AMg-2N that is used in corrugated sets of honeycomb panels for aircraft and spacecraft interiors. It is proved that the modes of treatment have a significant effect on the durability characteristics of the material since they predetermine the thickness of the defective layer at the obtained holes. An optimal choice of the pulse rate and the flow rate can reduce the width of the defective layer by 20–50 % and bring it down to 0.035 mm. Intensive cooling of the perforated zone can also eliminate cracking at the edges, thereby increasing the tensile strength up to 229 MPa, which is close to the strength value of the supplied material; meanwhile relative elongation remains virtually unchanged. The experimental research used LBC-400-5. The laser-jet stream was formed due to the original head design that minimizes the loss of the output power. The research has proved that deviation of the flashed hole from the circumference is minimized by an adjustment of the laser-jet head, i. e. combining the axes of the laser beam and the jet of fluid. The use of nozzles with profile cut (in the form of a rectangle with rounded corners, oval, or triangle) produces an appropriate shape of the holes, which is very important for manufacturing honeycomb panels with an aperiodically curvilinear corrugated-core structure.